1999
DOI: 10.1038/sj.bjc.6690544
|View full text |Cite
|
Sign up to set email alerts
|

Inverse association between breast cancer incidence and degree of visual impairment in Finland

Abstract: Summary A total of 10 935 women with visual impairment were identified from the Finnish Register of Visual Impairment and followed up for cancer through the Finnish Cancer Registry for years 1983-1996. Breast cancer risk decreased by degree of visual impairment (P for trend 0.04) which suggests a dose-response relationship between visible light and breast cancer risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
44
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(47 citation statements)
references
References 8 publications
2
44
0
1
Order By: Relevance
“…Our results are consistent with findings from Sweden (Feychting et al, 1998) and Finland (Verkasalo et al, 1999). However, we did not observe any decrease of breast cancer risk in the Norwegian women with milder degree of visual impairment, and in this respect our results correspond with the Swedish, but differ from the Finnish results.…”
Section: supporting
confidence: 90%
See 1 more Smart Citation
“…Our results are consistent with findings from Sweden (Feychting et al, 1998) and Finland (Verkasalo et al, 1999). However, we did not observe any decrease of breast cancer risk in the Norwegian women with milder degree of visual impairment, and in this respect our results correspond with the Swedish, but differ from the Finnish results.…”
Section: supporting
confidence: 90%
“…In totally blind people without ocular perception of light melatonin production is not suppressed by exposure to visible light, therefore a reduced risk of breast cancer could be anticipated. Studies from Sweden and Finland have shown a lower breast cancer risk in totally blind women compared to that of the general female population (Feychting et al, 1998;Verkasalo et al, 1999). A US case-control study also indicated that, overall, women with bilateral blindness had almost half the risk of developing breast cancer compared to the control group (Hahn, 1991).…”
mentioning
confidence: 99%
“…Pinheiro et al, 2006). Melatonin, which is secreted mainly from the pineal gland and plays a role in sleep duration, is suggested as one of the candidates responsible for the association in breast cancer (Brzezinski, 1997;Schernhammer and Schulmeister, 2004) as it influences the synthesis and secretion of sex hormones by promoting the release of gonadotropin-releasing hormone (Martin and Klein, 1976;Aleandri et al, 1996).In relation to melatonin, there have been several observational studies of night work, shift work or visual impairment, and sex hormone-related cancers such as prostate or breast (Feychting et al, 1998;Verkasalo et al, 1999;Kliukiene et al, 2001;Megdal et al, 2005;Kubo et al, 2006;Conlon et al, 2007;Schwartzbaum et al, 2007). However, there has been no study of sleep duration and prostate cancer risk, even though prostate cancer, like breast cancer, is also a sex hormone-related cancer.…”
mentioning
confidence: 99%
“…In relation to melatonin, there have been several observational studies of night work, shift work or visual impairment, and sex hormone-related cancers such as prostate or breast (Feychting et al, 1998;Verkasalo et al, 1999;Kliukiene et al, 2001;Megdal et al, 2005;Kubo et al, 2006;Conlon et al, 2007;Schwartzbaum et al, 2007). However, there has been no study of sleep duration and prostate cancer risk, even though prostate cancer, like breast cancer, is also a sex hormone-related cancer.…”
mentioning
confidence: 99%
“…In a recent case-control study of 93 cases and 185 controls comprising Israeli women matched by age and residential area, high risk of breast cancer has been found to be linked with substantial exposure to ALAN from outdoor illumination, whereas reduced risk has been detected among women exposed to moderate bedroom ALAN without noteworthy external exposures [154]. Finally, several studies that have assessed the relation between breast cancer risk and the degree of visual impairment suggest an inverse dose-dependent relation between the two variables, with significant decrease in breast cancer risk among completely blind women [155][156][157].…”
Section: Circadian Disruption and Breast Cancermentioning
confidence: 99%